2019
DOI: 10.5588/ijtld.18.0540
|View full text |Cite
|
Sign up to set email alerts
|

QuantiFERON®-TB Gold In-Tube reliability for immigrants with parasitic infections in Boston, USA

Abstract: SUMMARY SETTING: Accurate testing and treatment for latent tuberculosis infection is necessary for tuberculosis elimination. Certain parasite infections are associated with increased tuberculin skin test positivity; species-specific effects on QuantiFERON-TB Gold In-Tube (QGIT) are not yet described. OBJECTIVE: We sought to determine whether infection with helminths or protozoa affects QGIT results. DESIGN: We retrospectively analyzed QGIT and parasite testing results for immigrants screened in Boston fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…IGRAs have been developed more recently (13)(14)(15)(16)(17)(18). They are in vitro assays able to measure the blood levels of IFN-γ released by T lymphocytes stimulated with antigenic peptides of M. tuberculosis [14,[17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…IGRAs have been developed more recently (13)(14)(15)(16)(17)(18). They are in vitro assays able to measure the blood levels of IFN-γ released by T lymphocytes stimulated with antigenic peptides of M. tuberculosis [14,[17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The low sensitivity of the QFT-Plus in detecting TB disease cases has been well documented [13][14][15] , particularly in countries with a high prevalence of M. tuberculosis infection and other comorbidities 16,17 , such as Burkina Faso, which was one of our study sites. Additionally, there may be a potential correlation between the low sensitivity of the QFT-Plus and a high frequency of comorbidities, particularly parasitic infections and fecal yeast [18][19][20] , in these patients. Because the sensitivity of the QFT-Plus has been previously determined in countries with a low prevalence of M. tuberculosis infection and other comorbidities, including the US, Japan, and Australia 12 , the low sensitivity and high number of indeterminate results obtained with the QFT-Plus in this study may be due to the particularly poor health status of the Burkina Faso study participants.…”
Section: Discussionmentioning
confidence: 99%
“…A 2020 study of recent Chicago immigrants showed 6.4% and 4.0% seroprevalence for Toxocara and Strongyloides stercoralis [ 55 ]. A Boston study of refugees and asylum seekers in the USA from 2012 to 2017 found 0.2% hookworm infection and 1.9% S. stercoralis infection, [ 56 ]. Though the US Centers for Disease Control and Prevention has established protocols for testing and treating refugee populations in the USA, there are no surveillance protocols currently in place to address these infections in documented or undocumented immigrants [ 55 ].…”
Section: Vulnerable Groupsmentioning
confidence: 99%